The microPIXE technique to understand the distribution of heavy metals in arbuscular mycorrhizal symbiosis - Statello, Marina (2024)
Soil colloids tend to retain heavy metals (HMs), potentially reaching toxic concentrations. Phytoremediation, a decontamination technique, involves plants and their associated microorganisms to mitigate the toxicity of HMs in the environment. Most plant species employed in phytoremediation establish symbiotic associations with arbuscular mycorrhizal fungi (AMF). AMF can adsorb or uptake HMs through their hyphal network, translocating them towards the host plant1. Particle-induced X-ray emission with a micro-focused beam (microPIXE) enables the micrometric mapping of elements in a sample2, helping to determine the concentration and distribution of HMs. In this work, we used microPIXE to analyze the distribution and accumulation of copper (Cu) in structures of the AMF Rhizophagus intraradices GC3 strain associated to Ri T-DNA carrot roots under in vitro condition (Banco de Glomeromycota in vitro)3. This would enable us to understand the role of AMF in HM-polluted soils...